PENGARUH E-SERVICE QUALITY, BRAND IMAGE, DAN ETIKA BISNIS TERHADAP E-SATISFACTION PENGGUNA SHOPEE PADA MAHASISWA AKUNTANSI STIE CENDEKIA BOJONEGORO - Norma Rohadhatul; Siti Aisyah; Riska Andriani; Rahma Aliya (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2025)
This study aims to analyze the influence of e-service quality, brand image, and business ethics on consumer satisfaction. The research period was December 2024, employing a quantitative approach. Data collection was conducted using Google Forms. The population of this study consisted of Shopee e-commerce users among accounting students at STIE Cendekia Bojonegoro. The sampling technique used was quota random sampling, with a total of 44 respondents. Data analysis techniques included validity and reliability tests, normality tests, and multiple linear regression analysis. The results showed that all indicators were valid (p-value 0.000 < 0.05), and the instrument was highly reliable (Cronbach's Alpha 0.949). The normality test confirmed that the data were normally distributed (p-value > 0.05). The F-test indicated that the regression model was significant as a whole (p-value 0.000), while the t-test revealed that each independent variable (X1, X2, X3) had a significant partial effect on the dependent variable, consumer satisfaction (Y) (p-value < 0.05). In conclusion, e-service quality, brand image, and business ethics significantly influence consumer satisfaction, both simultaneously and partially